Solubilization of membrane proteins using ionic liquids - Francisco, Rafael Neves (2015)
The main goal of this work consists on the study of the ability of ionic liquids (ILs) to extract membrane proteins from biological membranes while keeping their integrity in aqeuous solutions. Since typical surfactants are mainly used for this purpose, ILs are here investigated as a new class of extraction agents. For the evaluation of the ILs solvation ability power, four proteins were selected to be overexpressed in Escherichia coli and to be used as model proteins, namely the Outer Membrane Protein F (OmpF) and Outer Membrane Protein C (OmpC), that are β-barrel proteins, and two bacteriorhodopsins, Haloarcula marismortui (HmBRI) and Haloarcula walsbyi (HwBR), that α-helix proteins. In this work, the investigations carried out with OmpC failed during cloning and OmpF failed during the purification step. On the other hand, the two bacteriorhodopsins were expressed and purified successfully. Although some adjustments (mainly the His-tag) must be performed to improve the expression and the purification level, 1 mg/L of HmBRI and 0.1 mg/L of HwBR were purified. The protein HmBRI was then chosen as a model protein to test the extraction ability of several aqeuous solutions of ILs. Its interesting feature of producing solutions and pellets with a purple colour, and its specific absorbance at 552 nm, make of HmBRI an excellent model protein since it can be easily monotired by Vis-spectroscopy and analysis of its colour. Iimidazolium-, phosphonium-and cholinium-based ILs were investigated in several concentrations in aqueous solutions. None of the ILs studied revelaed to be able to extract HmBRI without denaturation. However, cholinium decanoate was able to extract a higher amount of protein from the biological membrane compared to the commercial detergent decyl maltoside. Mixtures using cholinium decanoate and decyl maltoside were then used to extract the HmBR altough no further improvements on the extraction were observed. Since HmBRI is reported as a good fusion tag for other membrane proteins, avian specific antibodies (polyclonal) were finally produced by immunizing quails to evaluate the performance of HmBRI as a fusion tag.